Manual of skin diseases of the dog and cat - Paterson, Sue (Blackwell Pub., 2008)
Manual of Skin Diseases of the Dog and Cat, Second Edition provides a valuable asset to the practice library for quick and easy reference on a busy day. Dealing with all common skin diseases in both the dog and the cat, particular attention is paid to the differences between the two species. Each chapter looks at a different type of skin disease with descriptions of clinical presentations and a guide for diagnostic tests for each. This book is a combined update of two of Sue Paterson’s books, Skin Diseases of the Dog and Skin Diseases of the Cat, into one volume for ease of reference.